Computational fluid dynamics applied to mining engineering: a review - Xu, Guang; Luxbacher, K.; Ragab, S.; Xu, J.; Ding, Xuhan (2016)
This paper provides a review of computational fluid dynamics (CFD) applications in mining engineering, with particular focus on mine ventilation-related flow problems. The basic principles of CFD are reviewed and six turbulence models commonly used are discussed with some examples of their application and guidelines on choosing an appropriate turbulence model. General modelling procedures are also provided with particular emphasis on mesh independence study and CFD validation methods, which can further improve the accuracy of a model. CFD applications in mining engineering research and design areas are reviewed, which illustrate the success of CFD and highlight challenging issues. It is expected that more CFD research will be carried out to solve problems in mining engineering, and the potential benefits from the simulations are enormous if proper modelling procedures are followed and modern computational approaches are implemented.